The global solution to AI : risks, rhetoric, ideology, and psychoanalysis / Robert Samuels. - Samuels, Robert, 1961- (Palgrave Macmillan, 2025)
This text interrogates the notion that artificial intelligence may represent a threat to the world because it lacks both empathy and reason and suggests that - if we do not intervene to limit and control AI - we are at risk of being overtaken by machines, which are not aligned with human ethics and values. To outline how we should counter the worst tendencies of automated intelligence, we must first understand the roots of morality and reason and why we have been misunderstanding the fundamental difference between humans and computers. Moreover, by critiquing the rhetoric and ideology of AI proponents, we can gain a clear understanding of the need to regulate our machines on a global basis through global treaties.